Oral diabetic therapy in type 2 diabetes mellitus - Jasik, Mariusz; Dęmbe, Krzysztof; Karnafel, Waldemar (Przewodnik Lekarza/Guide for GPs, 2005)
The aim of article is to review the various therapeutic agents available for management of patients with type 2 diabetes and to suggest an approach to drug selection as monotherapy and in combination theraphy. There are now five classes of oral medications which are available in therapy of type 2 diabetes – sulfonylureas, glinides, biguanides, thiazolidinediones and alpha-glucosidase inhibitors. Each class of drugs works differently to treat impaired insulin secretion, insulin resistance and postprandial hyperglycemia. Application of the strategies and principles of oral diabetic therapy in type 2 diabetes should be individualised based on the degree of hyperglycemia, hyperinsulinemia or insulin deficiency.